Odpowiedź:
a)
-24 * √(5 1/16) + 12 * ∛(3 3/8) - 15√(2 14/25) = -24 * √25/16 + 12 * ∛27/8 -
- 15√64/25 = -24 * 5/4 + 12 * 3/2 - 15 * 8/5 = -30 + 18 - 24 = -54 + 18 = -36
b)
9 * ∛8/27 - 20 * √(1 9/16) + 4 : ∛64/125 = 9 * 2/3 - 20 * √25/16 + 4 : 4/5 =
= 6 - 20 * 5/4 + 4 * 5/4 = 6 - 25 + 5 = 6 - 20 = -14
c)
(-1/2)³ * √(7 1/9) - ∛(4 17/27) * (-1,8)² - 2²/15 = -1/8 * √64/9 - ∛125/27 * (-1 4/5)² -
- 4/15 = -1/8 * 8/3 - 5/3 * (-9/5)² - 4/15 = -1/3 - 5/3 * 81/25 - 4/15 = -1/3 - 27/5 - -4/15 = -5/15 - 5 2/5 - 4/15 = -9/15 - 5 6/15 = - 5 15/15 = 6
Szczegółowe wyjaśnienie: